Circular Innovation and Re-distributed Manufacturing - Moreno Beguerisse, Mariale; Charnley, Fiona; Court, Richard; Wright, Matt; Campbell, Callum (Cranfield University, 2017)
This is one of five feasibility studies conducted as part of the RECODE Network
Keywords: 'Consumer Goods'; EPSRC; 'RECODE Network'; 'Manufacturing Engineering not elsewhere classified'; 'Manufacturing Processes and Technologies (excl. Textiles)'; 'Manufacturing Management'; Re-distributed Manufacturing'